2020
DOI: 10.1002/acr.24074
|View full text |Cite
|
Sign up to set email alerts
|

Total Serum Testosterone and Western Ontario and McMaster Universities Osteoarthritis Index Pain and Function Among Older Men and Women With Severe Knee Osteoarthritis

Abstract: Objective. To investigate whether serum total testosterone level is associated with knee pain and function in men and women with severe knee osteoarthritis (OA). Methods. We enrolled 272 adults age ≥60 years (mean ± SD age 70.4 ± 4.4 years, 53% women) who underwent unilateral total knee replacement (TKR) due to severe knee OA. Serum testosterone levels and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain and function of the operated and contralateral knee were measured at 6-8 weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…The incidence of osteoarthritis increases with aging and appears to be associated with age-related declines in sex hormones, including estrogen and testosterone [ 22 ]. After menopause, women are reported to have incremental increases in osteoarthritis risk compared with men of the same age [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of osteoarthritis increases with aging and appears to be associated with age-related declines in sex hormones, including estrogen and testosterone [ 22 ]. After menopause, women are reported to have incremental increases in osteoarthritis risk compared with men of the same age [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Castrated male rhesus macaques exhibit severe joint osteoarthritis [ 31 ]. Furthermore, higher serum total testosterone concentrations are associated with less pain in elderly men and women with severe knee osteoarthritis [ 22 ]. Higher serum testosterone concentrations are linked to a higher level of LBM, including knee cartilage volume, which delays the damage to articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…age of 70.3 years found that a higher T level was associated with less knee disability in non-operated women and less pain (as determined by the Western Ontario and McMaster Universities Osteoarthritis Index) in normal-weight men (35). In another longitudinal investigation on the association between endogenous sex hormone levels and knee OA features and pain, T level was inversely associated with effusion-synovitis volume and pain score in female OA patients (36).…”
Section: Discussionmentioning
confidence: 94%
“…In our study, a nominally significant result for the relationship between serum DHT levels and risk of OA in women was found, while little evidence of the sex-specific association between serum T levels and OA was provided. However, a 2-year double-blind cross-sectional analysis of 273 seniors with severe knee OA at an average age of 70.3 years found that a higher T level was associated with less knee disability in non-operated women and less pain (as determined by the Western Ontario and McMaster Universities Osteoarthritis Index) in normal-weight men ( 35 ). In another longitudinal investigation on the association between endogenous sex hormone levels and knee OA features and pain, T level was inversely associated with effusion-synovitis volume and pain score in female OA patients ( 36 ).…”
Section: Discussionmentioning
confidence: 99%